2021
DOI: 10.1101/2021.03.08.433413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-healing codes: how stable neural populations can track continually reconfiguring neural representations

Abstract: Neural representations change, even in the absence of overt learning. To preserve stable behavior and memories, the brain must track these changes. Here, we explore homeostatic mechanisms that could allow neural populations to track drift in continuous representations without external error feedback. We build on existing models of Hebbian homeostasis, which have been shown to stabilize representations against synaptic turnover and allow discrete neuronal assemblies to track representational drift. We show that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 171 publications
(284 reference statements)
0
3
0
Order By: Relevance
“…To generate consistent perception, the visual system must cope with changes in the coding of visual information. 76,77 It has been suggested that a system that carries a high-dimensional distributed code may maintain its functionality under representational drift by either confining the drift to the null space of the code, or via a compensatory plasticity of the downstream reader. 29,32 In both cases, the similarities across representations of different stimuli are expected to be somewhat conserved over time, even under a significant change in the representations themselves.…”
Section: Discussionmentioning
confidence: 99%
“…To generate consistent perception, the visual system must cope with changes in the coding of visual information. 76,77 It has been suggested that a system that carries a high-dimensional distributed code may maintain its functionality under representational drift by either confining the drift to the null space of the code, or via a compensatory plasticity of the downstream reader. 29,32 In both cases, the similarities across representations of different stimuli are expected to be somewhat conserved over time, even under a significant change in the representations themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a closer scrutiny of the response of PPC neurons in the 'T-maze' task showed that drift is not confined to a "coding null space" (Rule, Loback, et al 2020). Hence, an adaptive readout mechanism which involves synaptic plasticity to track and compensate the drift is required to achieve stable behavior (Rule, Loback, et al 2020;Rule and O'Leary 2021). Whether and how such a mechanism is implemented in the brain remains an open question.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In any case it remains unclear precisely how behavior remains unaffected by the observed drift. One potential solution to this is to allow for compensatory plasticity in downstream circuits so as to stabilize the readout performance 30,48,[50][51][52] . Another is to seek some higher-order population structure which remains stable in the face of ongoing RD 19,21,22,27,48,49 .…”
Section: Discussionmentioning
confidence: 99%